Building Blocks for Effective Macroprudential Policies in Latin America : Institutional Considerations - Imam, Patrick (IMF Working Papers; Working Paper, 2012)
An increasing number of countries - including in Latin America - are reforming their financial stability frameworks in the aftermath of the financial crisis, in order to establish a stronger macroprudential policy function. This paper analyzes existing arrangements for financial stability in Latin America and examines key issues to consider when designing the institutional foundations for effective macroprudential policies. The paper focuses primarily on eight Latin American countries, where the institutional arrangements for monetary and financial policies can be classified in two distinct groups: the "Pacific" model that includes Chile, Colombia, Peru, Costa Rica, and Mexico, and the "Atlantic" model, comprising Argentina, Brazil, and Uruguay.